Farmers' Motivations and Barriers to Participation in the Rice Farming Insurance Program (AUTP) in Kulon Progo Regency Indonesia - Dhika Cahyasita; Fadilla Ristya Aminda; Mawar Kusumawardani (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2025)
Farming Business Insurance Program (AUTP) in Kulon Progo Regency, a disaster-prone area in the Special Region of Yogyakarta, Indonesia. Data were collected between July and August 2024 through a structured survey of 93 rice farmers, comprising 48 participants and 45 non-participants of the AUTP program. The results show that overall knowledge of the program remains low, with only 29% of respondents demonstrating a high level of understanding. Key motivations for participation include directives from farmer group leaders, peer influence, support from agricultural extension officers, and perceived production risks. In contrast, significant barriers include insufficient information about registration procedures and a perceived lack of need for insurance. These findings underscore the need for targeted awareness campaigns, enhanced extension services, and streamlined administrative processes designed explicitly for disaster-prone farming communities. By integrating social influence factors and environmental risk contexts, this study provides policy-relevant insights for enhancing farmer engagement in agricultural insurance schemes such as AUTP.